Hypertension Control among Adult Iraqis - Khaleefah , Muna A; Al-Badri, Husham J.; Mousa, Nada A. (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Hypertension is a chronic illness that affects one billion people both in high and low-income countries and is the most common risk factor for death throughout the world. It is also responsible for stroke, ischemic heart disease, heart, and kidney failure in addition to its huge effect on the economy. Like many developing countries, Iraq is undergoing a transitional epidemiological period with increasing burden of hypertension and its contributing risk factors e.g. unhealthy diet, physical inactivity, obesity, hyperglycemias, hypercholesterolemia, and smoking. In spite of the availability of a screening program for the early detection of hypertension in primary health care centres (PHCCs) little data on hypertension control is available.Objectives: Assessing blood pressure control rate among Iraqi adults 18 years and older, and identifying the related determinants.Patients and Methods: The study is derived from the second round of Non-Communicable Diseases Risk Factors STEPS survey Iraq 2016. A cross-sectional survey was performed on households from all Iraqi governorates excluding three governorates suffering instability. A Multi-stage cluster sampling technique for a sample of 4120 Iraqi adults was used. Interviews were held from the first week of November for 20 days using Arabic and Kurdish translated versions of STEPS questionnaire. A total of 4071 residents participated.Results: the prevalence of hypertension/ high blood pressure was 35.6%. Only 7.9% were under medication and controlled with an evident sex-based difference in favour of women (9.3% vs. 6.6% respectively). Uncontrolled blood pressure increased with age (t=7.4 p=